Enhancing the conversational agent with an emotional support system for mental health digital therapeutics - Wang, Qing; Peng, Shuyuan; Zha, Zhiyuan; Han, Xue; Deng, Chao; Hu, Lun; Hu, Pengwei (Frontiers in Psychiatry, 2023)
As psychological diseases become more prevalent and are identified as the leading cause of acquired disability, it is essential to assist people in improving their mental health. Digital therapeutics (DTx) has been widely studied to treat psychological diseases with the advantage of cost savings. Among the techniques of DTx, conversational agent can interact with patients through natural language dialog and has become the most promising one. However, conversational agents' ability to accurately show emotional support (ES) limits their role in DTx solutions, especially in mental health support. One of the main reasons is that the prediction of emotional support systems does not extract effective information from historical dialog data and only depends on the data derived from one single turn interaction with users. To address this issue, we propose a novel emotional support conversation agent called STEF-agent that generates more supportive responses based on a thorough view of past emotions. The proposed STEF-agent consists of Emotional Fusion Mechanism and Strategy Tendency Encoder. Emotional Fusion Mechanism focuses on capturing the subtle emotional changes throughout a conversation. Strategy Tendency Encoder aims at foreseeing strategy evolution through multi-source interactions and extracting latent strategy semantic embedding. Experiment results on the benchmark dataset ESConv demonstrate the effectiveness of STEF-agent compared with competitive baselines.